Employability and Work Life of People with Disabilities in Higher Education Sector - S, Dr. Barani Daran (South Eastern European Journal of Public Health, 2025)
This review-based article focuses on examining theoretical cum research-based literature pertaining to topic of employability and work life for disabled persons in higher education sector. It also investigates about research studies on the topic of views of academicians regarding the employability and professional life of persons with health-related debilities in the higher educational institutions. Author of this intellectual work has given his perspectives on topics related to employability and work life of persons with disabilities in higher educational organizations of “India”. An examination of the available literature regarding employability and work life of individuals with disabilities indicates a deficiency of both review based and research related literature on this topic, both in “India” and at international level. There is a scarcity of qualitative research studies, both in “India” and foreign countries, that elucidates the viewpoints of current and former educators in the higher education sector regarding the theme of this article. Challenges mentioned by the author concerning employment opportunities for disabled individuals in “India's higher educational sector”, consists of restricted job prospects for them in both central and state universities as well as hesitance of private higher educational institutions to provide work opportunities for such individuals. Views of author regarding problems faced by employees with health-related debilities in “Indian higher education institutions”, include inadequate infrastructure accommodating the needs of staffs with chronic health limitations, inconsistent implementation of work flexibility tailored to specific health limitations of such employees, insufficient support from supervisors cum colleagues, etc. Recommendations in this scholarly endeavour would enhance the employability of individuals with disabilities and elevate their quality of work life within the context of “Indian higher education”.